Carbohydrate intake in young female cross-country skiers is lower than recommended and affects competition performance - Kettunen, Oona; Mikkonen, Ritva; Mursu, Jaakko; Linnamo, Vesa; Ihalainen, Johanna K. (Frontiers in Sports and Active Living, 2023)
Purpose (1) To evaluate if energy availability (EA), macronutrient intake and body composition change over four training periods in young, highly trained, female cross-country skiers, and (2) to clarify if EA, macronutrient intake, body composition, and competition performance are associated with each other in this cohort. Methods During a one-year observational study, 25 female skiers completed 3-day food and training logs during four training periods: preparation, specific preparation, competition, and transition periods. A body composition measurement (bioimpedance analyzer) was performed at the end of the preparation, specific preparation, and competition periods. Competition performance was determined by International Ski Federation (FIS) points gathered from youth national championships. Results EA (36–40 kcal·kg FFM−1·d−1) and carbohydrate (CHO) intake (4.4–5.1 g·kg−1·d−1) remained similar, and at a suboptimal level, between training periods despite a decrease in exercise energy expenditure (p = 0.002) in the transition period. Higher EA (r = −0.47, p = 0.035) and CHO intake (r = −0.65, p = 0.002) as well as lower FM (r = 0.60, p = 0.006) and F% (r = 0.57, p = 0.011) were associated with lower (better) FIS-points. CHO intake was the best predictor of distance competition performance (R2 = 0.46, p = 0.004). Conclusions Young female cross-country skiers had similar EA and CHO intake over four training periods. Both EA and CHO intake were at suboptimal levels for performance and recovery. CHO intake and body composition are important factors influencing competition performance in young female cross-country skiers.